Collection and sharing of genomic and health data for research purposes: Going beyond data collection in traditional research settings (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
In the recent years collection of health and genomic data for biomedical research purposes has been expanded beyond traditional research settings. In doing so, various online tools and platforms are being utilized to collect data from various sources including Electronic Health Records, mHealth applications, disease registries and patient generated databases. While there is relatively higher certainty regarding the legal grounds for processing health and genomic data in the traditional research setting, the questions remain about the applicable legal framework when collecting data from other sources. In addition, given the diverse nature of collected data, adhering to traditional care-research distinction to determine the applicable legal requirements is confronted with complexities. This is particularly the case when data collected in the care setting are being later used for research purposes. In this article, we discuss the challenges associated with governance of processing data collected outside research settings and underline the steps should be taken to ensure conformity of such data processing by the applicable data protection regulations.
Keywords: Genomic data; biomedical research; mHealth; Real-World Data; GDPR